Information and Communication Technology Management Strategy to Support the Digital Transformation of SMP Negeri 1 Bolaang - Rompas, Parabelem Tinno Dolf; Sumampow, Zoya Febrina; Subagio Manggopa; Meyvilia Yohana; Wa Ode Siti Cutriani (International Journal of Information Technology and Education, 2025)
Digital transformation in schools has become a strategic necessity to improve the quality of learning services, governance, and competitiveness of educational institutions. This study aims to analyze appropriate Information and Communication Technology (ICT) management strategies to support the acceleration of digital transformation at SMP Negeri 1 Bolaang. The research method uses a literature review by analyzing empirical findings and current theories regarding ICT management, digital transformation, technology governance, and digital leadership. The results of the study indicate that the success of digital transformation in schools is largely determined by strategic ICT planning aligned with the school’s vision, strengthening digital infrastructure, improving the digital competence of teachers and education personnel, implementing good digital governance, and participatory change management. This study confirms that a structured and holistic ICT management approach can improve administrative efficiency, learning quality, and data-driven decision-making at SMP Negeri 1 Bolaang. Research recommendations include increasing human resource capacity, establishing a school digital transformation unit, and utilizing a collaborative ecosystem to accelerate digitalization.